El Imperio Hitita. Características esenciales y cauces de desarrollo de una organización imperial hegemónica del Oriente Próximo (II milenio a.C.) - González Salazar, Juan Manuel (Gerión. Revista de Historia Antigua, 2003)
The present article illustrates and summarizes some aspects of the formation of the Hittite Empire in the second millennium B.C. We shall delineate briefly the gradual progress of the Hittite Kingdom which —as a living organism— emerged (in the seventeenth century B.C.) flourished and fell (early in the twelfth century B.C.) The Hittites were dominant power their homeland and peripheral territories werw located. They incorporated a large number of Anatolian vessols in the far west and controlled big zones of northern Syria (the Hittite authority reached the Euphrates river in the east), exactly in the fourteenth-thirte- enth centuries B.C. It will be attempted to show the configuration of the Hittite imperial structure, with its degree of political and military organisation, key pieces to understand the maintenance of their empire during a long time.